Local Aphrodisiac Plants Available in Sikkim Himalaya for Male Infertility (Traditional Aspects, in vivo and in vitro Evidences): A Review Insight - Khatiwara, Sagarika; Khar, Tiewlasubon Uriah; Bhutia, Sonam (Pharmacognosy Reviews)
Objectives: This review aims to know the status and gaps in male infertility and enhancement measures in term of traditional utility, In vitro & in vivo studies. Methodology: The data were collected through an extensive literature search from reputed online databases such as PubMed, ScienceDirect, ResearchGate, Google Scholar, Willy, 1library and Core. Results: The results were summarized in the tables and figures. Through an extensive review where a minimum of 20 local plants including 16 Families were identified with 20 genus wise distribution-Malveaceae and Zingiberaceae, Fabaceae and Poaceae (10%) are frequently used plant families were summarized in Table 1. Roots are the maximum part used followed by seeds and the powdered form of preparation is most consumed. The mood of preparation and their dosage forms were also discussed. Conclusion: These plants play a great role in treating infertility issues in males and will continue to be treated in a large populace. However, there is a gap in the studies on ethnomedicinal plants used as a fertility enhancer in males from the northeast part of India, mainly from Sikkim and other states. Therefore, in-depth studies are needed from the landscape to improve the issues of infertility in males and its physiological mechanism.
Keywords: Local Aphrodisiac; Fertility enhancer; Male; Medicinal plants; Traditional medicinal; Fertility Management; Sikkim Himalaya